THE USE OF SOCIAL MEDIA PLATFORMS TO FACILITATE ENGLISH LEARNING: A SURVEY OF GAYONESE UNIVERSITY STUDENTS - Munandar, Imam (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
Social media is a technological advancement in information and communication used by people of all ages and around the globe. Even though social media platforms were not initially designed for education, they have captured the attention of some educators, particularly those who teach and study the English language. This study aimed to determine what kinds of social media English students at the State Institute of Islamic Studies Takengon utilize and how social media assists students in learning English. In this study, a descriptive-qualitative methodology was employed. The researcher used open-ended response surveys, interviews, and written records to collect data. This research utilized data analysis techniques involving data reduction, presentation, conclusion, and verification. To ensure the validity of the information, the writer employed both reliability and source triangulation mechanisms. According to the findings of this study, students improved their English skills by utilizing eight different social media platforms, including Blogger, Facebook, LinkedIn, WhatsApp, Telegram, YouTube, Instagram, and TikTok. In comparison, most students prefer media-sharing platforms (MMS) to social networking sites (SNS) to enhance their English skills. Students mainly use social media features such as viewing videos, listening to podcasts, and conversing with native English speakers. In addition, they also utilize personal chat, group chat, comment sections, photos, descriptions, stories, and biographies to enhance their English skills through peer interaction. The study's conclusions may have an impact on curriculum development, instructional strategies, and educational policies that support language acquisition and cross-cultural communication in digital environments, both within and outside of Gayonese universities.